2020
DOI: 10.4018/ijvple.2020070106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Blended Learning Method on Students' Achievement in English and Their Motivation Towards Learning It

Abstract: The purpose of this study is to investigate the effect of using a blended learning method on ninth grade students' achievements in English and their motivation towards learning it. The sample consisted of 100 female students selected purposefully and distributed into two groups: experimental and control. The experimental group studied English through a computerized program in the traditional method, while the control group was taught by the traditional method only. The results revealed statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
2
11
0
2
Order By: Relevance
“…This result of the study may be attributed to the multiple advantages of the blended learning strategy expected to serve students' learning and contribute to improving their level, including this type of learning allows the learner to review his educational material and study it more than once without feeling boredom at the time he wants and in the place he desires, and this in its entirety increases his motivation to learn, which increases his direct academic achievement. The method of learning using the blended learning strategy is a new method for students, which has aroused their interest and increased their learning motivation, and this is confirmed by the results of the previous studies such as Hazmi (2018), whose results show that the use of blended learning increases the motivation and achievement of students, and learning through the blended learning strategy is based on the merging between abstract theoretical knowledge and practical application with what it provides in terms of colors, animations, and sounds. In other words, these matters may give an educational impact greater than the effect given by written words and enable the student to employ linguistic knowledge from all walks of life.…”
Section: Discussionsupporting
confidence: 59%
“…This result of the study may be attributed to the multiple advantages of the blended learning strategy expected to serve students' learning and contribute to improving their level, including this type of learning allows the learner to review his educational material and study it more than once without feeling boredom at the time he wants and in the place he desires, and this in its entirety increases his motivation to learn, which increases his direct academic achievement. The method of learning using the blended learning strategy is a new method for students, which has aroused their interest and increased their learning motivation, and this is confirmed by the results of the previous studies such as Hazmi (2018), whose results show that the use of blended learning increases the motivation and achievement of students, and learning through the blended learning strategy is based on the merging between abstract theoretical knowledge and practical application with what it provides in terms of colors, animations, and sounds. In other words, these matters may give an educational impact greater than the effect given by written words and enable the student to employ linguistic knowledge from all walks of life.…”
Section: Discussionsupporting
confidence: 59%
“…Kumar et al (2016) mentioned that students reported the effectiveness of interactive learning in promoting and improving active participation, group discussion, and understanding. Hijazi and AlNatour (2020) found that students' motivation to learn using traditional methods of learning was very low when compared to other methods and consequently their scores were very low too. Meguid and Collins (2017) found that interactive learning promoted students' interaction, focused attention, clarified information, and provided feedback.…”
Section: Discussionmentioning
confidence: 96%
“…Afrasiabifar and Asadolah (2019) revealed that students were more satisfied with an interactive style compared to traditional lectures. Hijazi and AlNatour (2020) found that it is important to provide students with different types of activities that suits their style of learning, and this is not possible when using the traditional method of learning especially that the teacher is considered as the cornerstone while the student is a passive recipient most of the time. In addition, Taha et al (2014) stated that the traditional teaching approaches used informative, receptive, and reproductive methods while interactive and creative methods promoted students' motivation, enhanced problem-solving skills, and encouraged logical and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Penggunaan ke dua cara tersebut dapat juga disebut sebagai blended learning. Blended learning merupakan konsep revolusioner yang mencangkup pengajaran di kelas tradisional (classroom lesson) dan online learning (Hijazi & AlNatour, 2020) (Keshavarz & Hulus, 2019). Penggunaan model blended learning dengan menggunakan e-learning saat pembelajaran online yang terintegrasi dan terstruktur akan membuat proses pembelajaran berlangsung lebih bermakna (Rahman et al, 2020).…”
Section: Pendahuluanunclassified